Energy Allocation Algorithm for Energy Harvesting Wireless Sensor Network (International Journal of Scientific Research and Management (IJSRM), 2015)
the life-time of wireless sensor network can easily be prolonged very significantly, with the use of energy harvesting technologies. The energy management policy of an energy harvesting WSN take into account the energy replenishment process, unlike a traditional WSN powered by nonrechargeable batteries. In this paper, we present a study about the energy allocation for transmission and sensing in an energy harvesting sensor node with a finite buffer and rechargeable battery. The aim of the sensor node is to maximize the total data transmitted in a finite horizon subject to channel fading, energy harvesting rate and energy availability in the battery. Here in this paper we present a energy distribution algorithm using dynamic programming for energy allocation problem. We conduct simulations to compare the performance between our proposed algorithm and the existing algorithm from[1]. Simulation results show that the proposed algorithm achieves a higher throughput than the existing algorithm under different settings.